2022
DOI: 10.3389/fnana.2022.995286
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical and psychological considerations in temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) is the most common form of focal epilepsy and is associated with a variety of structural and psychological alterations. Recently, there has been renewed interest in using brain tissue resected during epilepsy surgery, in particular ‘non-epileptic’ brain samples with normal histology that can be found alongside epileptic tissue in the same epileptic patients — with the aim being to study the normal human brain organization using a variety of methods. An important limitation is that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 216 publications
0
2
0
1
Order By: Relevance
“…Human and animal data also indicate hilar cell loss following SE and epilepsy ( Covolan and Mello, 2000 ; Rojas et al, 2021 ; DeFelipe et al, 2022 ). Our findings suggest that following OP-induced SE, in the chronic phase, hilar neuronal loss was not necessarily indicative of the development of epilepsy.…”
Section: Discussionmentioning
confidence: 98%
“…Human and animal data also indicate hilar cell loss following SE and epilepsy ( Covolan and Mello, 2000 ; Rojas et al, 2021 ; DeFelipe et al, 2022 ). Our findings suggest that following OP-induced SE, in the chronic phase, hilar neuronal loss was not necessarily indicative of the development of epilepsy.…”
Section: Discussionmentioning
confidence: 98%
“…Synaptic density measurement are a useful tool to describe the synaptic organization of a particular area, nuclei and even layers in different brain regions, but also the degree of connectivity underlying the computational properties of a given brain area or in a given brain network. Meanwhile numerous studies in various animal species and brain regions have performed such an analysis but data for a density of synaptic complexes in humans are still rare (but see Marco and DeFelipe 1998; Tang et al 2001; DeFelipe et al 1999, 2002; Alonso-Nanclares et al 2008; Blazquez-Llorca et al 2013; Finnema et al 2016; Cano-Astorga et al 2021, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…MFS (Franck et al, 1995;Proper et al, 2000;Buckmaster et al, 2002;Buckmaster, 2014) and cell loss in the hilus region of the dentate gyrus (Covolan and Mello, 2000;Rojas et al, 2021;DeFelipe et al, 2022) is reported in both human epilepsy and animal models of epilepsy. Following SE, hippocampal mossy fibers of dentate granule cells are said to develop recurrent collaterals that invade the dentate IML to generate recurrent excitation by forming granule cell-granule cell synapses (Mello et al, 1993;Okazaki et al, 1995).…”
Section: Discussionmentioning
confidence: 99%